Effets de certaines mesures de la deuxième entente des médecins omnipraticiens sur leur activité dans le cadre du régime d’assurance-maladie - Boutin, Jean-Guy (L'Actualité économique, 1980)
AbstractDesigned to contribute to an assessment of the effects of the second agreement with general practitioners, the study analyzes the effects produced on the medical practices of general practitioners by pay range of a) the individual income ceiling and b) various types of fee restrictions on supplementary medical procedures provided under the agreement.The methodology used consisted basically in analyzing the variations of selected indicators of professional activity and medical practice among general practitioners by pay range following the implementation of the second agreement. Control groups were used to facilitate the assessment of other factors that may have influenced the variations referred to.The study shows that the income ceiling has resulted in a significant slowdown in the professional activity of general practitioners whose income had been in excess of the income ceiling in the year preceding the agreement. The shorter work period was accompanied by a longer vacation period.From the second part of the study it appears that the implementation of the second agreement has also appreciably reduced differences in medical procedures by pay range. The fee restrictions on supplementary procedures have produced a very considerable drop in the number of supplementary procedures performed by general practitioners in the top pay ranges, whereas in the past such procedures had been particularly prevalent in those pay ranges.